THE EFFECT OF JOB STRESS, WORKLOAD, AND CAREER DEVELOPMENT ON EMPLOYEES' TURNOVER INTENTION AT PT XYZ, MEDAN BRANCH - Vanisia Putri Barus; Yeni Absah; Evawany Yunita Aritonang (Journal Analytica Islamica, 2025)
This study aims to analyze the effect of job stress, workload, and career development on turnover intention among employees at PT XYZ, Medan Branch. The research employs a quantitative approach using multiple linear regression analysis. Data were collected through questionnaires and processed using SPSS version 30. The sample consisted of all 32 employees of PT XYZ, Medan Branch. The results indicate that, partially, job stress has a positive and significant effect on turnover intention. Similarly, workload has a positive and significant effect on turnover intention, while career development has a negative and significant effect on turnover intention. Furthermore, the findings reveal that job stress, workload, and career development simultaneously have a significant effect on turnover intention. These results suggest that increased job stress and workload tend to raise employees' intention to leave the company, whereas effective career development opportunities can reduce such intentions. Therefore, organizations should manage workload appropriately, reduce job-related stress, and provide clear career development opportunities to minimize employees' turnover intention.